Mapping wordnets from the perspective of inter-lingual equivalence - Rudnicka, Ewa (2018)
This paper explores inter-lingual equivalence from the perspective of linking two large lexico-semantic databases, namely the Princeton WordNet of English and the plWordnet (pl. Słowosieć) of Polish. Wordnets are built as networks of lexico-semantic relations between words and their meanings, and constitute a type of monolingual dictionary cum thesaurus. The development of wordnets for different languages has given rise to many wordnet linking projects (e.g. EuroWordNet, Vossen, 2002). Regardless of a linking method used, these projects require defining rules for establishing equivalence links between wordnet building blocks, known as synsets (sets of synonymous lexical units, i.e., lemma-sense pairs). In this paper an analysis is carried out of a set of inter-wordnet relations used in the mapping of the plWordNet onto the Princeton WordNet, and an attempt is made to relate them to equivalence taxonomies described in specialist literature on bilingual lexicography and translation.